The Effect of Scaffolding-Assisted Project-Based Learning Model on the Creative Writing Skills of Narrative Texts Among 7th-Grade Students at SMP Negeri 5 Denpasar - Gusti Made Dwi Jayanti; Ida Bagus Putrayasa; I Putu Mas Dewantara (GoAcademica Research & Publishing, 2026)
This study aims to analyze the differences and the effect of the scaffolding-assisted Project-Based Learning (PjBL) model on the narrative text creative writing skills of 7th-grade students at SMP Negeri 5 Denpasar. The study was motivated by students' low writing proficiency, evidenced by the fact that 60% of students struggled to develop ideas, structure plotlines, and use appropriate language. The experiment used quasi-experimental design specifically the Nonequivalent Pretest-Posttest Control Group Design. The population consisted of all 7th grade students totally (273 individuals), and the sample was selected using cluster random sampling: Class VII A (39 students) served as the experimental group receiving scaffolding-assisted PjBL, while Class VII B (40 students) served as the control group taught using a model involving lectures, assignments, and presentations. The narrative text creative writing assessment instrument utilized a rubric with a 0–20 scale (maximum score of 20); this instrument was validated by experts and demonstrated a Cronbach's Alpha reliability coefficient of 0.76. Data were analyzed using the Independent Samples T-test to determine differences in creative writing skills between the experimental and control groups, and the Analysis of Covariance (ANCOVA) test to examine the effect of the scaffolding-assisted PjBL model while controlling for students' initial ability based on pretest scores. Hypothesis testing results showed a significance value (2-tailed) of 0.000 (p<0.05), indicating a significant difference in creative writing skills between the two groups. The average post-test score for the experimental class was 16.38 (Good category), higher than that of the control class, which scored 14.65 (Fair category). Improvements in writing quality were observed across all indicators, including content, organization, vocabulary, language use, and writing mechanics. The study concludes that the scaffolding-assisted Project-Based Learning model is effective and significantly improves the creative narrative writing skills of 7th-grade students at SMP Negeri 5 Denpasar; therefore, it is recommended as an innovative instructional alternative to address the issue of students' low creative writing proficiency.